Skilled Personnel Supply and the Prospects for Regional Innovative Development in Poland - Gajdos, Artur; Żmurkow, Edyta (Comparative Economic Research. Central and Eastern Europe, 2013)
The aim of this paper is to analyze the supply of highly qualified personnel in the context of prospects for the future innovative development of voivodships in Poland. Analysis of these problems and the relationship between them will be based on the studies on the educational profile of regions and on the analysis of potential trends and possibilities of creating a highly skilled labor force coming from higher education system, as well as on the research on the innovation level and profile of particular voivodships. Furthermore, analysis of possibilities and the level of knowledge diffusion will be conducted.